2017
DOI: 10.1002/ecy.2031
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐damage biomass allocation and not invasiveness predicts tolerance to damage in seedlings of woody species in Hawaii

Abstract: Plant-herbivore interactions have been predicted to play a fundamental role in plant invasions, although support for this assertion from previous research is mixed. While plants may escape from specialist herbivores in their introduced ranges, herbivory from generalists is common. Tolerance traits may allow non-native plants to mitigate the negative consequences of generalist herbivory that they cannot avoid in their introduced range. Here we address whether tolerance to herbivory, quantified as survival and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 81 publications
(174 reference statements)
0
15
0
Order By: Relevance
“…We implemented an artificial folivory treatment to simulate the effects of heavy folivory, a common approach in the study of tolerance to herbivory (Marquis , Tiffin and Inouye , Ashton and Lerdau , Vergés et al , Lurie et al ). Phragmites australis lineages vary widely in resistance to folivory (Cronin et al , Bhattarai et al ) and, consequently, it would have been difficult to achieve a standardized level of herbivory among source populations without varying herbivore density and/or exposure time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We implemented an artificial folivory treatment to simulate the effects of heavy folivory, a common approach in the study of tolerance to herbivory (Marquis , Tiffin and Inouye , Ashton and Lerdau , Vergés et al , Lurie et al ). Phragmites australis lineages vary widely in resistance to folivory (Cronin et al , Bhattarai et al ) and, consequently, it would have been difficult to achieve a standardized level of herbivory among source populations without varying herbivore density and/or exposure time.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanisms underlying tolerance to herbivory are varied but relatively understudied (Tiffin , Moreira et al , Siddappaji et al , Krimmel and Pearse , Quijano‐Medina et al ). Plant traits like high photosynthetic rates, growth rates, belowground storage and branching are thought to promote compensatory growth, and therefore tolerance (Meyer , Strauss and Agrawal , Tiffin , Lurie et al ). Life‐history traits like longer lifespan and investment in belowground also have been linked to tolerance (Krimmel and Pearse ).…”
Section: Introductionmentioning
confidence: 99%
“…In this Special Feature, Lurie et al. () investigate plant traits associated with the seedling tolerance of invasive and noninvasive tree species in Hawaii, and demonstrate that predamage growth patterns determine tolerance independent of species’ invasiveness status. Their finding supports the view that the same tolerance mechanism may act early in life for both invasive and noninvasive woody species, and might be generalizable to some extent across species.…”
Section: New Avenues For Understanding Tolerancementioning
confidence: 99%
“…Regardless of the evolution of increased competitive ability (EICA) hypothesis (Blossey and N€ otzold 1995) stating that invasive species have improved their competitive ability because of changes in resource allocation as a response to lack of native herbivores, surprisingly little is known about tolerance relative to species invasiveness. In this Special Feature, Lurie et al (2017) investigate plant traits associated with the seedling tolerance of invasive and noninvasive tree species in Hawaii, and demonstrate that predamage growth patterns determine tolerance independent of species' invasiveness status. Their finding supports the view that the same tolerance mechanism may act early in life for both invasive and noninvasive woody species, and might be generalizable to some extent across species.…”
Section: New Avenues For Understanding Tolerancementioning
confidence: 99%
“…Numerous studies have indicated that the biomass allocation patterns of plant organs are size‐dependent (McConnaughay & Coleman, ; Niinemets, ; Wright & McConnaughay, ). However, many other studies have used proportional changes to reflect herbivory tolerance or compare the tolerances of different species (Araminiene, Varnagiryte‐Kabašinskiene, & Stakenas, ; Lurie, Barton, & Daehler, ; Stevens et al, ; Wang, Bezemer, van der Putten, Brinkman, & Biere, ; Wang et al, ; Zvereva, Lanta, & Kozlov, ). The ratios used to test biological hypotheses may change with plant size and cannot accurately measure the relationship between herbivory tolerance and biomass allocation.…”
Section: Introductionmentioning
confidence: 99%